The France's Interest in Southern Algeria and Attempts to Separate the Sahara: A Critical Study (مجلة الواحات للبحوث والدراسات, 2026)
This article explores France’s colonial interest in the Algerian Sahara, driven by its strategic location and resources. Beginning in the late 18th century, European powers, including France, sought control over trade routes and natural wealth. After occupying Algeria in 1830, France expanded into the Sahara through military, economic, and cultural means, including alliances with local tribes and Christian missionary activities. Following the discovery of oil and gas, France attempted to separate the Sahara from Algeria to maintain control over these resources. However, Algeria's unity and resistance ultimately prevented the success of these colonial efforts.